Sri Lanka Development Forum : The Economy, Regional Disparities, and Global Opportunities - World Bank (Washington, DC, 2012)
This report is intended to inform the discussions of the Sri Lanka Development Forum. Specifically, section One reviews recent economic performance, the status of macroeconomic management and the strategic directions outlined in Mahinda Chintana. It notes that the recent acceleration in Sri Lanka's growth can be partly attributed to large aid flows for tsunami reconstruction and to rapid growth in domestic demand. While Sri Lanka can sustain higher growth given its level of human development and integration with global markets, this will require addressing structural constraints and managing the downside risks associated with rising inflation and the escalating conflict. Section Two of the report addresses the regional disparities in growth and poverty reduction in Sri Lanka. Noting that differences in education levels and access to infrastructure cannot fully explain the sharp gaps in regional growth, it suggests that the limited scope of market reforms in key sectors, such as agriculture, has played a more significant role. In particular, policy reforms in agriculture have been elusive, partly due to misperceptions that they will hurt the poor. Progress in reducing regional disparities will require politically-sensitive reforms that address these misperceptions, through inter alia public consultations. Finally, section Three takes up the question of how Sri Lanka can accelerate growth further by taking advantage of its high levels of educational attainment and tapping global opportunities in the information technology (IT) and knowledge sectors. The recent increase in foreign direct investment in telecommunications, IT, and business process off-shoring (BPO) in banking suggest that there is potential for such growth. This potential can be enhanced by moving further on the policy agenda that removes the obstacles facing a knowledge economy